2019
DOI: 10.1186/s13000-019-0841-1
|View full text |Cite
|
Sign up to set email alerts
|

BCL2 overexpression: clinical implication and biological insights in acute myeloid leukemia

Abstract: Background BCL2 protein inhibitor venetoclax (ABT-199) has been authorized by Food and Drug Administration for relapsed/refractory chronic lymphoid leukemia with 17p deletion. Although venetoclax/ABT-199 also caused cell death in acute myeloid leukemia (AML), whether it could be applied to clinical treatment needs further studies. Here, we revealed clinical implication of BCL2 overexpression in de novo adult AML, and may provide theoretical basis for targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 41 publications
4
40
2
Order By: Relevance
“…Despite the association of the high expression of ARHGAP9 with CN-AML, no relationship between ARHGAP9 expression and prognosis of CN-AML was found in the current study. In addition, several studies have shown that abnormal expression of some genes such as NCALD, IL2RA , and BCL2 are associated with prognosis in AML patients with auto/allo-HSCT and/or chemotherapy [ 41 43 ]. Our findings showed that ARHGAP9 high groups had poor prognosis in post-chemotherapy AML patients, whereas no significant differences in OS and EFS were found between the ARHGAP9 high group and ARHGAP9 low group in patients who underwent after auto/allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the association of the high expression of ARHGAP9 with CN-AML, no relationship between ARHGAP9 expression and prognosis of CN-AML was found in the current study. In addition, several studies have shown that abnormal expression of some genes such as NCALD, IL2RA , and BCL2 are associated with prognosis in AML patients with auto/allo-HSCT and/or chemotherapy [ 41 43 ]. Our findings showed that ARHGAP9 high groups had poor prognosis in post-chemotherapy AML patients, whereas no significant differences in OS and EFS were found between the ARHGAP9 high group and ARHGAP9 low group in patients who underwent after auto/allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Differential expression analysis for RNA/miRNA sequencing data was calculated using the raw read counts with the R/Bioconductor package “edgeR”, all analyses were controlled for the false discovery rate (FDR) by the Benjamini–Hochberg procedure [ 24 ]. The miRNA which could target LEP was identified by the venn analysis ( http://bioinformatics.psb.ugent.be/webtools/Venn/ ) of three websites miRDB ( http://mirdb.org/miRDB/ ), miRWalk ( http://mirwalk.umm.uni-heidelberg.de/ ) and TargetScan ( http://www.targetscan.org/vert_72/ ) [ 25 , 26 ]. All basic statistical analyses were performed using the base functions in R version 3.4 ( https://www.r-project.org ).…”
Section: Methodsmentioning
confidence: 99%
“…Bcl-2 is often overexpressed in AML patients, both at diagnosis as well as at relapse and can render resistance to cytotoxic chemotherapeutics [271,272]. A major finding by Lagadinou et al identified high levels of Bcl-2 as a feature of LSCs to maintain mitochondrial integrity for survival [27].…”
Section: Pi3k/akt/mtor Inhibitors In Combination With Bcl-2 Inhibitorsmentioning
confidence: 99%